2018
DOI: 10.1111/iji.12408
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of ABO and RHD blood group antigens in blood donors in Burkina Faso

Abstract: Geographical distribution of ABO and RHD antigens is important for blood transfusion services and population genetics studies. There are few data on this topic in Burkina Faso, a multi‐ethnic country. Our study aims at reporting phenotypic and allelic frequencies of ABO and RHD blood groups among voluntary blood donors from various ethnical regions of Burkina Faso. We conducted a cross‐sectional study including 81,486 blood donors. ABO allelic frequencies were determined using the Bernstein method. Differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
(32 reference statements)
2
6
1
Order By: Relevance
“…The Burkinabe (n=21) had O>B>A with the absence of AB. This agrees with a study done in Burkina Faso [55], in the higher incidence of O. The AB blood group is the least proportion of the ABO blood group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The Burkinabe (n=21) had O>B>A with the absence of AB. This agrees with a study done in Burkina Faso [55], in the higher incidence of O. The AB blood group is the least proportion of the ABO blood group.…”
Section: Discussionsupporting
confidence: 92%
“…There were no previous references about the ABO in Eritrea. However, it agrees with most African people, which have a higher incidence of O blood group [48,50,55]. The Ghanaian (n=9) had O>B with the absence of the A and AB.…”
Section: Discussionsupporting
confidence: 78%
“…However, there are slight regional variations of ABO blood groups, where in some studies on the continent; as some studies carried out in Western and Central Africa showed that blood group B was predominant to blood group A. For example, studies conducted in Guinea [ 19 ], Ghana [ 20 ], Nigeria [ 21 ], Burkina Faso [ 22 ], and Congo [ 22 ]. Similar findings were reported from India [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The distribution characteristics of ABO and RhD blood groups varies in different regions and races. [ 1 – 3 ] Earlier studies have reported the percentage of O blood group to be 34.0% in China, but 46.6% in the USA. [ 4 , 5 ] The percentage RhD-negative blood has reported to be 1.0% in China, but 14.6% in the USA.…”
Section: Introductionmentioning
confidence: 99%